Gender, Dividen Tunai Dan Nilai Perusahaan Pada Perusahaan Kesehatan Yang Terdaftar Di Bursa Efek Indonesia Pada Krisis Covid-19 - Ella Rahmayanti (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to find out whether gender and cash dividends influence company value. This research was conducted on Health sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2020 period. The population in this study was 13 companies and the sample in this study was 6 companies using purposive sampling as the sampling method. Data collection is carried out through financial report data published on the official IDX website, namely www.idx.co.id. The research results showed that gender has a negative effect on firm value, cash dividend has a positive effect on company value, and liquidity as a control variable has a positive effect on firm value.